The Roman Republican wreck Ilovik–Paržine 1, island of Ilovik (Croatia), Preliminary report - Miholjek, Igor; Boetto, Giulia; Poveda, Pierre; Divić, Anton; Vidulić, Ivan; Dugonjić, Pavle; Dumas, Vincent (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
Discovered in 2016 in the bay of Paržine, Ilovik Island (Croatia), the wreck Ilovik–Paržine 1 has been systematically excavated by a joint Croatian and French team from 2018 to 2021. It was a mortise-and-tenon built sailing ship of about 20–22 m in length, transporting a cargo of Adriatic Greco-Italic amphoras containing wine and timbers. Its last voyage took place between to the 2nd or 3rd quarter of the 2nd century BC. Thanks to the ballast, the rear third of the ship was better preserved than the bow, part of which was found about 20 m to the east. The ship has a typical Hellenistic hull design (a cross-section with a wine-glass profile), and the large mortise on the easternmost end of the keel could be related to a specific ship shape characterized by nearly vertical stem.